OBSERVATIONS ON THE MARINE PLANKTON IN THE GULF OF KUTCH, OFF PORT OKHA - Bhaskaran, M; Gopalakrishnan, P (Indian Journal of Fisheries, 2011)
The quantitative and qualitative distribution of marine plankton off Port Okha, inthe Gulf of Kutch, are dealt with in this paper.The monthly displacement volume of plankton varies from 3.8 to 14.6 ml. Thephyto-plankton shows a primary peak in September. Secondary peaks in January orJune are instances of local blooms of more than one genus and species of diatoms. Theprimary peak of 1970 is the result of an autochthonous bloom of Chaetoceros spp. Thediatoms form the bulk of phytoplankton and the dinoflagellates are scarce.The zooplankton also shows a similar bimodal distribution; the primary peakoccurring either in October or April and the secondary peak in March or December.